Experimental study of quality and electricity losses in low voltage rural electric networks - O. S. Rakhimov; D. N. Mirzoev; E. I. Grachieva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Due to the increase in the number of farms in the Devashtichsky district of the Sughd region of Tajikistan, over the past 3-4 years, a disproportionate distribution of electricity in the 0.4 kV network has been observed. Unbalance currents of phase loads in relation to asymmetric phase voltages at the terminals of consumers of a three-phase network cause additional losses of electricity, which can reach 21% of the standard losses. In the decree of the President of the Republic of Tajikistan dated May 10, 2009 No. 29 “On energy saving and reduction of electricity losses” it is indicated that there is a need to study the quality of electricity in rural 0.4 kV networks and its compliance with GOST 32144. 2013, as well as an assessment of losses electricity in its distribution structure is an important task in the field of rural electricity. METHODS. A single-line diagram of a 0.4 kV network with initial parameters, which were refined during the survey of the network, and the current loads of outgoing lines were investigated. Experimental studies of the quality of electricity and assessment of the level of losses in the low- voltage network were carried out using a complex measuring device «Energotester» PKE - A - C4. RESULTS. The studies allowed obtaining data on the daily consumption of electricity in individual outgoing lines, information on the characteristics of consumers, digital information (database) on indicators of the quality of electricity in low-voltage networks. CONCLUSIONS. It has been established that the main factors influencing the losses of electricity in low-voltage networks are: incommensurability of the power of transformers of transformers and consumers, uneven loading of individual phases, a significant effect of individual converters on the quality of energy. Measures are forecasted to reduce losses and improve the quality of electricity in low-voltage rural networks of 0.4 kV.